Determinación de la riqueza específica de la familia Orchidacae en plantaciones de café área de conservación municipal Almendra Moyobamba - Sarmiento Ocmin, Jacqueline (2009)
The present thesis, "Determination of the Specific Wealth of the Family Orchidaceae in plantations of brown Area of Conservation Municipal Almendra Moyobamba- San Martin", this guided to contrihute in the identification ofthe specific wealth ofthe Orchids that you/they have like I inhabit epifito to the plantations of coffee, considering that the plants of more coffee to nine years of antiquity present Jiquenes and mosses I propitiate for the species of orchids, that which will be a potential of commercial interest and of investigation. This having in consideration that our Department of San Martín is one of the main producers of coffee, having varieties of coffee in the study area Jike: Caturra, Catimor and National, that lvhich many of these plantations of coffee harbar 38 species of orchids that it will serve as value added to the production of co:ffee benefitting the farmers ofthe study area. Through a proposal of a Plan of Handling of the species of Orchids in the Area of Conservation Municipal Almendra, will be good for a sustainable use ofthe resource. At the moment the illegal trade of Orchids, the demographic explosion, the indiscriminate deforestation and he/she bums ofthe forests, they are contributing to the pi11aging ofvaluable species that you/they have not been investigated still, this puts in danger the e"A'tinction of our Natural Resources, which should stop as soon as possible stops this way to avoid that it continues getting lost our flora. In tum Organizations that support the farmers for the rational use of the Natural Resources existas: The German Technical Cooperation (GTZ-PDRS), I Govem Regional of San Martin, Project Special High May (PEAM), National Institute of Natural Resources (lNRENA), Entity Prestadora of Services of Reparation EPS-M. SRLtda, Rural Beats, among others. For the analysis ofthe reality ofthe Area of Conservation Municipal Almendra, was carried out by means of the processes of Determ:ination of the area, Revision and validation of the existent information, Summary of the information, Elaboration of speci:fic studies, Identification of the plots of land with plantations of coffee, Determination of the quantity of spec!es of orchids in the pJantations of coffee, Ch<;rracterization of the veg~tation, determination of indexes of the biological diversity, Position of plots of land in plantations of coffee, Proposal of a Plan of Handling with administration measures for a sustainable use of the resource Orchid. Through the use of diagrams of bars it \vill allow to visualize the abundance of plants of Orchids for species in the two varieties of coffee as Caturra and National and the abundance of species of orchids by means ofthe index ofMargalef, as well as the distribution of the Diameter to the Height of Chest (DAP) for the species of opposing plants near the plantations of coffee. In the Area of Conservation Municipal Almendra, was identified 38 species of Orchids in the 35 plots of land of sampling in plantations of coffee with a 9 year-old antiquity I inhabit favorable to harbor many species of orchids for the liquenes presence and mosses,. being the most representative the species Macroclinium aurorae in the plantations of national coffee and caturra with 213 plants and with smaller presence the species Diadenium sp. with 2 plants of orchids of a total of 860 plants of Orchids. The distribution of the flora in the study of the vegetation presents 89 species at the 35 plots of land that which a bigger DAP average the species Almond with a 72.61 present cm at the plots ofland 31 and ·32, and with smaller DAP the species Laurel with a 5.56 present cm at the plots ofland 1, 2, 16, al)d 20 and with an older average DAP spicy offruit tree Mango \vith 25,83 present cm atthe plots of land 1,3,4,9,25,28 and 34 and with smaller DAP the spice banana with 10,32 present cm at the plots of land 2,12,14,16,18,19,20,23 and 27. Finding more presence of plants of the gender Inga that surround as shade to the plants of coffee. The Present work of investigation of the Determination of the Specific Wealth of the F amily Orchidaceae in plantations of coffee, will be a document it guides for the taking of decisions in what refers to a Plan of handling of the species of Orchids in the Area of Conservation Municipal Almendra Department of San Martin, as comes him carrying out the Region Loreto with a Concerted Regional Program of Agrobiodiversidad and its Plan of Action, yvith t~e _ purpose ofto conserve and to take advantage ofthe natural resources in a sustainable way.